Characteristic Indices of Young Men's Neck Based on Collar Fitness (Journal of Fiber Bioengineering and Informatics, 2012)
This research carries out non-touched anthropometric measurements on 200 male university studentsaged from 19-26. 10 measurements relevant to the body neck were drawn in considering the necessarymeasurements in the pattern design of the fashion collar, This research utilizes the SPSS software tocarry out a frequency distribution analysis and cluster analysis for the sample. 5 characteristic indiceswere elected in a statistical approach. These characteristic indices provide more reference measurementsto the structural design of the men's fashion collar, it can be used to serve as the establishment ofspecification series for men's wear and for ready-to-wear production.